Financial Management for MSMEs and Farmer Groups in the District of Kamang Magek: Pengelolaan Keuangan bagi UMKM dan Kelompok Tani di Kecamatan Kamang Magek - Anne Putri; Eka Risma Putri; Renita Astri; Emi Handriana; Adriani Adnani; Layla Hafni; Dona Ikranova; Yulianda Nofika Sari; Siti Maryam (Journal of Community Service and Application of Science, 2022)
Small and medium enterprises (SMEs) and farmer groups are a source of the community's economy in Kamang Magek District. SMEs are engaged in various fields such as food and processed products, crafts and carvings, furniture, agricultural and animal husbandry products, while farmer groups in Kamang Magek District also vary from horticultural crops, food crops and plantation crops. In the Livestock sector, there are also poultry livestock, both broiler and laying eggs, small and large ruminants as well as processed agricultural and livestock products. Several SMEs and farmer groups in the Kamang Magek sub-district raised the local wisdom of Kamang Magek, such as kamang crackers, kamang coffee, Kamang duck, Kamang mangosteen, embroidery, and kamang special furniture. Currently, SMEs and Farmer Groups are experiencing difficulties in developing their businesses due to business capital constraints and most of them are even trapped in loans with high interest rates. SMEs have not been able to determine the amount of working capital they need for business development, they do not take into account the size of the loan with their production capacity or business results, so the amount of loans made does not match the actual funding or working capital needs. This has resulted in the amount of the loan submitted being too large in excess of requirements or the amount of the loan being too small so that it is not sufficient for business needs. To overcome this problem, it is necessary to provide counseling to SMEs and farmer groups regarding financial management.